The Role of the Environmental Activities Community in the Management of Plastic Waste in Blahbatuh Village, District Blahbatuh, Gianyar Regency - I Made Dwiantara; Ida Ayu Putu Sri Widnyani (Ekuitas: Jurnal Pendidikan Ekonomi, 2022)
Community is a social group that unites itself consisting of several people who have similarities in terms of needs, beliefs, talents, interests and hobbies so as to create a sense. The purpose was to determine the role of the environmental activist community in the management of plastic waste and to determine the factors that support and hinder the role of the environmental community in plastic waste management. This study use qualitative descriptive approach. The theory used is Role Theory     according and also uses Implementation Theory. The results of this study indicate that the role of the environmental community in managing plastic waste has not been carried out optimally, community activities are in accordance with Bali Governor Regulation No. 97 of 2018. The factors that support are community participation in plastic waste processing activities and good cooperation between environmental activist communities while the factors that hinder or become obstacles are limitations.